Overcoming or overstepping? Boundary infrastructure for learning in the context of continuous improvement research-practice partnership - Angel X. Bohannon; Caitlin C. Farrell; Spencer Cook (Frontiers in Education)
IntroductionUnder federal policy guidelines, school districts are increasingly expected to engage with research evidence to guide their efforts around instructional improvement. This article explores how a continuous improvement research-practice partnership (CI RPP) can create opportunities for educators to learn new research-based ideas and practices.MethodsWe present a year long case study of two rural school districts engaged in a CI RPP focused on math instruction.ResultsWe focus show how research-based mathematics ideas introduced by research partners were taken up by teachers, school leaders, instructional coaches, and district leaders. Then we describe how the county office of education created important opportunities for learning through a boundary infrastructure: the network of people, practices, and objects that supported the movement of ideas between research, practice, and CI communities.DiscussionWe highlight the possibilities of county offices as critical actors in CI efforts. We also highlight how the county office’s efforts to broker knowledge did not involve just overcoming or transcending boundaries but also maintaining them when they perceived external partners to be “overstepping.”